STUDY THE SERUM LEVELS OF IL-17, IL-23 , TLR-4 ,TLR-7 ROLE IN IMMUNOPATHOGENESIS IN PATIENTS WITH PSORIASIS - Hamad Abood , Abdulla; Hussein Al-Saadi , Hassan Ali (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: The purpose of this study is to examine the relationship between immunological markers (IL-17, IL-23, TLR-4, and TLR-7) and several socio-demographic parameters, including age, sex, disease severity, stress, smoking behaviors, BMI classification, and dietary preferences, in patients with psoriasis.Methods: This study investigates the incidence of psoriasis among patients at Imam Al-Hussein City Hospital in Karbala, Iraq, during the period spanning from December 2022 to April 2023. The study encompassed a heterogeneous sample of individuals, comprising both individuals in optimal health and those who had recently received a diagnosis but had not yet commenced therapy. The research employed a case-control design with convenience sample and evaluated four anatomical regions using the Psoriasis Area and Severity Index (PASI) scoring system. The sandwich enzyme-linked immunosorbent assay (ELISA) technique was employed to conduct an inquiry on immunomarkers.Results: The analysis reveals a higher prevalence of psoriasis patients (50) compared to the control group (40), with no significant differences in age or gender. The female population had a numerical superiority, accounting for 56 of the total, while the male population had 35. There was a significant difference in body mass index (BMI) values between healthy controls and psoriasis patients, but statistically distinguishable differences. Smoking prevalence was significantly higher in psoriasis patients compared to the general population. Both groups exhibited adherence to a nutritionally balanced diet, with most patients presenting moderate intensity symptoms. Immunological markers, including IL-17, IL-23, TLR-4, and TLR-7, were found to be elevated in psoriasis patients compared to healthy individuals, suggesting a potential association between these markers and the disease's aetiology. Conclusion: Psoriasis patients make up a significant part of the study population, with higher smoking, stress, and healthy food habits. There's no significant difference in BMI, disease severity, or immunological markers.